A Paradigm of Calendaring‐Driven Electrode Microstructure for Balanced Battery Energy Density and Power Density (Adv. Energy Mater. 2/2023). Issue 2 (13th January 2023) - Zhan, Renming; Ren, Dongsheng; Liu, Shiyu; Chen, Zhengxu; Liu, Xuerui; Wang, Wenyu; Fu, Lin; Wang, Xiancheng; Tu, Shuibin; Ou, Yangtao; Ge, Hanlong; Wong, Andrew Jun Yao; et al.
Abstract : Electrode Microstructure In article number 2202544, Yongming Sun and co‐workers show that rational electrode microstructure design can promote fast lithium‐ion diffusion and electron transport, and their recombination, enabling high energy density and power density for lithium‐ion batteries.